2014
DOI: 10.1088/1751-8113/47/36/365101
|View full text |Cite
|
Sign up to set email alerts
|

Separation of particles leading either to decay or unlimited growth of energy in a driven stadium-like billiard

Abstract: Abstract. A competition between decay and growth of energy in a time-dependent stadium billiard is discussed giving emphasis in the decay of energy mechanism. A critical resonance velocity is identified for causing of separation between ensembles of high and low energy and a statistical investigation is made using ensembles of initial conditions both above and below the resonance velocity. For high initial velocity, Fermi acceleration is inherent in the system. However for low initial velocity, the resonance a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 68 publications
0
2
0
3
Order By: Relevance
“…One may find in the literature examples of FA that may present transport distinct from the normal diffusion, as exponential [3][4][5][6], ballistic [7,8] or even slower growths [9,10]. Also, interesting FA applications can be found in research areas such as plasma physics [11][12][13], astrophysics [14,15], atom-optics [16,17], and especially billiard dynamics [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…One may find in the literature examples of FA that may present transport distinct from the normal diffusion, as exponential [3][4][5][6], ballistic [7,8] or even slower growths [9,10]. Also, interesting FA applications can be found in research areas such as plasma physics [11][12][13], astrophysics [14,15], atom-optics [16,17], and especially billiard dynamics [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…For periodic oscillations it has been shown that the average energy/velocity is scaling invariant with respect to the control parameters as well as the time and it has well defined scaling exponents [22]. Furthermore, recent studies have shown that the existence of stick regions around the periodic orbits can influence the unlimited energy growth as well as the diffusion process [23,24]. Dissipation can also be considered either during the flight or upon collision.…”
Section: Introductionmentioning
confidence: 99%
“…Chamaremos de alta energia, o ensemble com velocidade inicial V 0 > V r , e o ensemble de baixa energia será para V 0 < V r . uma densidade maior de pontos, ao redor de algumas ilhas de estabilidade sugerindo que a ressonância entre a rotação ao redor de um ponto fixo e a perturbação externa, levou a partícula a ter um comportamento de umaórbita em um regime de stickiness [32,31,129,138].…”
Section: Velocidade De Ressonânciaunclassified
“…Acreditamos que o comportamento deórbitas em regime de stickiness aliado com a ressonância, seja o mecanismo responsável pelo decréscimo de velocidade da partícula [138], quando evoluímos a dinâmica em função do número de colisões com a fronteira móvel convergente, com um ensemble de baixas energias (V 0 < V r ), onde muitasórbitas decrescem de velocidade, e ficam estacionárias em um platô. Nessa evolução dinâmica, como uma parte siginificativa do espaço de fasesé acessível, quando asórbitas ficam presas em regime de stickiness, existe uma grande possibilidade de que ela mude de comportamento, ou seja, passe para dentro da ilha de estabilidade.…”
Section: Stickinessunclassified
See 1 more Smart Citation